Pemberdayaan Masyarakat Dalam Perspektif Ekonomi Islam - Ansori, Teguh (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This article aims to describe the concept and implementation of community empowerment in the context of Islamic economics. Community empowerment has an important impact in achieving the sustainable development goals, and a better understanding of. Community empowerment is a solution to the inequality and powerlessness felt by some people by the oppression of the powerful. Western economies provide no answer to this powerlessness. In an economic perspective, Islam provides a solid foundation to guide empowerment efforts. This research method is qualitative descriptive taken from several literatures. This research explores relevant Islamic economic principles, community empowerment implementation strategies, and their impact on economic and social well-being. The results of this study show that community empowerment in an Islamic perspective must use several instruments, namely zakat, infak, shodaqah, and waqf.